Pelatihan Peningkatan Fleksibilitas Tubuh Menggunakan Teknik Passive Stretching Dan PNF (Proprioceptive Neuromuscular Facilitation) Pada Atlet PPLP Papua - Sutoro Sutoro; Tri Setyo Guntoro; Dewi Nurhidayah; Ansar CS; Ipa Sari Kardi (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
The purpose of this service is to provide "Training to Increase Body Flexibility Using Passive Stretching Techniques and PNF (Proprioceptive Neuromuscular Facilitation) for PPLP Papua Athletes". The methods used in community service are lectures and demonstrations packaged in the form of training. Participants in this service were 30 PPLP athletes from 12 sports. The place for the dedication is at the student education and training center (PPLP) located in Doyo. The stages in this community service consist of three stages, namely preparation and planning, implementation of community service according to the results of coordination, the third is monitoring and evaluation. Evaluation of activities is carried out by looking at the achievement of the service carried out. The instruments used were questionnaires and direct observation. Data analysis techniques use descriptive statistics with percentage formulas. The results of the training showed that the participants were able to understand the material presented by the presenter and were able to practice the demonstrations carried out by the presenter.